Plotting as a Tool to justify the Psychological and Physical Torture in J. M. Coetzee’s ‘Waiting for the Barbarians’: Unveiling the Brutality: Analyzing Psychological and Physical Torture in J. M. Coetzee’s ‘Waiting for the Barbarians’ (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present paper is a deep study of the Imperialist rule in an ‘unknown land’ described in J. M. Coetzee’s ‘Waiting for the Barbarians’ and particularly aims to look at the unjust and inhuman ways adopted by them to protect and shield their power as well as the Empire’s physical boundaries. The research paper also intends to study the physical and mental atrocities done on the native people and the awful effects of this treatment on the innocent and naive people.